Tantangan dan Solusi dalam Peningkatan Literasi Membaca Anak Usia Dini - Widya Agustina; Syamsiah Depalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The integration of Civic Education (PKn) values ​​in modern society has become an urgent need Early childhood reading literacy is an important foundation in developing children's academic, cognitive, and social abilities. Although awareness of the importance of literacy has increased, practice in the field shows that many early childhood children still do not have adequate reading interest and skills. Various challenges such as limited access to books, low parental involvement, dependence on digital technology, and lack of teacher training are obstacles to improving early childhood literacy. Therefore, strategic and collaborative solutions are needed that involve families, schools, and communities in creating a child-friendly literate environment. This paper aims to comprehensively explore the existing challenges and present solutions that can be practically applied in supporting the improvement of early childhood reading literacy.